2013
DOI: 10.1016/j.joep.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Underweighting rare events in experience based decisions: Beyond sample error

Abstract: Recent research has focused on the "description-experience gap": While rare events are overweighted in description based decisions, people tend to behave as if they underweight rare events in decisions based on experience. Barron and Erev (2003) and Hertwig, Barron, Weber, and Erev (2004) argue that such findings are substantive and call for a theory of decision making under risk other than Prospect Theory for decisions form experience. Fox and Hadar (2006) suggest that the discrepancy is due to sampling error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 25 publications
(22 reference statements)
2
49
1
Order By: Relevance
“…The CSP, by design, represents a case of risk, as the objective probabilities are available to the subjects through sampling experience. 3 Among the previous studies, only the study by Barron and Ursino ( 2013 ) investigated the description-experience gap under risk (their experiment 1). However, their study made inferences only about the relative weightings of rare outcomes under DFE compared with those under DFD but not about the actual over- or under-weighting of rare outcomes under DFE.…”
Section: Relation To Previous Dfe Literaturementioning
confidence: 99%
“…The CSP, by design, represents a case of risk, as the objective probabilities are available to the subjects through sampling experience. 3 Among the previous studies, only the study by Barron and Ursino ( 2013 ) investigated the description-experience gap under risk (their experiment 1). However, their study made inferences only about the relative weightings of rare outcomes under DFE compared with those under DFD but not about the actual over- or under-weighting of rare outcomes under DFE.…”
Section: Relation To Previous Dfe Literaturementioning
confidence: 99%
“…One finding arising from such comparisons is that small probabilities appear to be underweighted in experience-based choice (Barron & Erev, 2003)-not overweighted, as is typical in decisionsfrom-description (Gonzalez & Wu, 1999;Prelec, 1998;Kahneman & Tversky, 1979). Given this divergence between decisions-from-experience and those from description, researchers have sought to understand how people use experience to inform their choices (Barron & Ursino, 2013;Dutt & Gonzalez, 2012;Erev et al, 2010;Lejarraga, Hertwig, & Gonzalez, 2012).…”
mentioning
confidence: 99%
“…Indeed, earlier studies show that experience-based decisions often have limited correspondence with decisions that are based on explicit a-priori probabilities. Specifically, it has been shown that people are less averse to losses Risk assessment under perceptual ambiguity 5 and may even prefer risky option when decisions are made based on subjective experience (Barron & Erev, 2003;Barron & Ursino, 2013;Erev & Barron, 2005;Erev, Ert & Yechiam, 2008;Jessup, Bishara & Busemeyer, 2008;Weber, Shafir & Blais, 2004;see Hertwig & Erev, 2009 for a review). This latter kind of deviation from an optimal decision-making strategy may occur due to the payoff-variability effect.…”
Section: Introductionmentioning
confidence: 99%